An Unusually Large Globular Submandibular Duct Sialolith A Rare Case Report - Dimple Sahni; Pervej MK; Gill K (GMC Patiala Journal of Research and Medical Education, 2018)
Sialoadenitisand sialolith are the most common diseases of the salivary gland and its duct. In 80 % of cases it is seen in submandibular gland and its duct (Wharton duct). Usually size of the sialolith is less than 10 mm and most commonly seen in middle aged male patient. Giant submandibular duct sialolith is usually elongated in shape ,globular is rare one. Here we going to discuss a case of unusually large (2.5cm x1.5cms)submandibular duct stone. Patient presented with pain and swelling in the floor the mouth. Clinical diagnosis was confirmed by CT scan floor of the mouth and neckand surgical management was done. Here, we are also we describing short overview of aetiology , clinical presentation diagnostic modalities, treatment option of submandibular sialolith . The aim of this study is to report a case of giant globular stone near the opening of whartons duct.